Penggunaan System E-filling untuk Penyampaian Surat Pemberitahuan Wajib Pajak Orang Pribadi - Selfiani, Selfiani; Lumbantobing, Sabar Pardamean; Rachmawati, Arifah; Surya, Patricia Kartika (Jurnal Manajemen dan Bisnis, 2024)
This research aims to investigate the influence of tax sanction and e-filing system utilizing with internet comprehension as moderator variable to taxpayer compliance in conveying the individual notification letter (SPT). Data of this research was collected by using questionnares (primary) given to taxpayers are at KPP Pratama Kebayoran Baru Tiga with simple random sampling method, while the method of data analyzing used deskriptive statistical tests, the quality of data test, normality test, multicoliniearity test and heteroscedastisity test. The method of analysis used multiple regression analysis, in the hypothesis test are multiple coefisien determination test, t test and f test. moderated regression analysis.The result of this research showed that tax sanction does not give the significant influences to taxpayer compliance, While the e-filing system utilizing gives significant influences to taxpayer compliance, so does the internet comprehension strengthens the relationship between the e-filing system utilizing to taxpayer compliance.